Collimated gamma rays from laser wakefield accelerated electrons - Minghua Li; Liming Chen; Dazhang Li; Kai Huang; Yifei Li; Yong Ma; Wenchao Yan; Mengze Tao; Junhao Tan; Zhengming Sheng; Jie Zhang (Matter and Radiation at Extremes, 2018)
Betatron radiation from laser wakefield accelerated electrons and X-rays scattered off a counter-propagating relativistic electron bunch are collimated and hold the potential to extend the energy range to hard X-ray or gamma ray band. The peak brightness of these incoherent radiations could reach the level of the brightest synchrotron light sources in the world due to their femtosecond pulse duration and source size down to a few micrometers. In this article, the principle and properties of these radiation sources are briefly reviewed and compared. Then we present our recent progress in betatron radiation enhancement in the perspective of both photon energy and photon number. The enhancement is triggered by using a clustering gas target, arousing a second injection of a fiercely oscillating electron bunch with large charge or stimulating a resonantly enhanced oscillation of the ionization injected electrons. By adopting these methods, bright photon source with energy over 100 keV is generated which would greatly impact applications such as nuclear physics, diagnostic radiology, laboratory astrophysics and high-energy density science.